A mechatronic test-bench to investigate the impact of ventricular pulsation in hydrocephalus. (May 2022) - Castelar Wembers, Carlos; Flürenbrock, Fabian; Maurer, Benedikt; Benninghaus, Anne; Radermacher, Klaus; Leonhardt, Steffen
Highlights: Intracranial system simulation of CSF space coupled to cardiovascular pulsation. Flexible in silico parameter setting and modular brain phantom. Electromechanical model of the test bench with Lagrange formalism. Silicon brain phantom with electrical properties for bioimpedance applications. Abstract: Background: In vitro modelling of the intracranial pressure (ICP) profile is an important tool to test potential prototypes for the diagnosis and treatment of hydrocepahlus. Objective: Here, a novel feedback-controlled mechatronic test-bench, which replicates the pulsatile ICP wave, is presented. Methods: The design is based on a MATLAB Simscape simulation of the intracranial system (ICS) and a test environment consisting of a linear actuator coupled to a metal bellows that deliver an ICP wave profile to the inner ventricular cavity of a silicon-gel-carbon brain phantom. The proposed approach applies the Lagrange formalism for the electromechanical modelling of the system. MATLAB's Grey-Box system identification tool is used and a PID controller is implemented. The ICS simulation is adapted from existing models from literature. A physiological aortic pressure wave is the input of the system. Results: The ICS model is able to generate wave profiles of varying morphology according to model parameters such as vessel compliance, capillary resistance and cerebrospinal fluid production rate. The wave profile serves as the reference pressure, ICPref, for the controller. Finally, the hardware setup successfully delivers the ICP profile to the intracranial cavity, ICPmeas, measured by a pressure sensor connected to the internal cavity of the brain phantom. Conclusion: The detailed in silico ICS model with cardiovascular coupling integrated with a modular brain phantom allows for flexible test scenarios in contrast to purely hydraulic setups. Future work will focus on the optimization of the test-bench for the validation of specific prototypes in the field of hydrocephalus.